Thermosetting adhesive composition, laminate film, and connection body and method for manufacturing the same

The thermosetting adhesive composition, featuring an epoxy resin, elastomer, and curing accelerator, addresses the issue of increasing shear viscosity over time, enabling efficient curing under low temperatures and extending the usable period for semiconductor module manufacturing.

JP2025044538APending Publication Date: 2025-04-02RESONAC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023152161
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Conventional thermosetting adhesive compositions used in semiconductor module manufacturing exhibit increased shear viscosity over time, limiting their usable period to about two weeks, which is not suitable for long-term use.

Method used

A thermosetting adhesive composition containing an epoxy resin, an elastomer, and a curing accelerator that generates a heterocyclic amine compound upon heating, which suppresses the rise in shear viscosity over time.

Benefits of technology

The adhesive composition allows for sufficient curing under low temperature conditions while maintaining stable shear viscosity over an extended period, ensuring a longer usable life and improved manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044538000004
    Figure 2025044538000004
  • Figure 2025044538000005
    Figure 2025044538000005
  • Figure 2025044538000006
    Figure 2025044538000006
Patent Text Reader

Abstract

To provide a thermosetting adhesive composition which sufficiently progresses a curing reaction under a low temperature condition, and can sufficiently suppress rise with the passage of time of shear viscosity.SOLUTION: There is provided a thermosetting adhesive composition. The thermosetting adhesive composition contains an epoxy resin, an elastomer, and a curing accelerator. The curing accelerator is a compound generating a heterocyclic amine compound by heating.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a thermosetting adhesive composition, a laminated film, and a connection body and a method for producing the same. [Background technology]

[0002] Conventionally, a semiconductor device is manufactured through the following steps. First, a dicing step is performed with a semiconductor wafer attached to a dicing adhesive sheet, thereby dividing the semiconductor wafer into individual semiconductor chips. Then, a pick-up step, a die bonding step, a wire bonding step, a molding step, and the like are performed. Patent Document 1 discloses an adhesive sheet (die-bond dicing sheet) that has both a function of fixing a semiconductor wafer in a dicing step and a function of bonding a semiconductor chip to a substrate in a die bonding step. Patent Document 2 discloses an adhesive sheet that acts as a dicing tape in a dicing step, has excellent connection reliability in a step of bonding a semiconductor element to a support member, and retains sufficient fluidity after heat history in wire bonding. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-288170 A [Patent Document 2] JP 2009-209345 A Summary of the Invention [Problem to be solved by the invention]

[0004] Incidentally, in recent years, with the evolution of semiconductor modules for small devices such as smartphones, the manufacturing process of semiconductor modules has also changed significantly from the conventional one. For example, the practical application of processes that do not perform dicing and die bonding processes is being promoted. Accordingly, the thermosetting adhesive composition used in the manufacturing process of semiconductor modules is also required to have different performance from the conventional one. In addition to this situation, the present inventors assumed that a material with relatively low heat resistance would be used in the semiconductor module, and proceeded with the development of a thermosetting adhesive composition in which the curing reaction proceeds sufficiently under low-temperature conditions of 100°C or less. When improvements were made based on a conventional thermosetting adhesive composition that has excellent low-temperature curing properties, it was found that although the development goal for low-temperature curing was achieved, the shear viscosity tends to increase over time. If the shear viscosity increases over time, the usable period after preparation is limited to about two weeks, so there is a demand for a longer usable period of the thermosetting adhesive composition.

[0005] A primary object of the present disclosure is to provide a thermosetting adhesive composition in which the curing reaction proceeds sufficiently under low temperature conditions and in which an increase in shear viscosity over time can be sufficiently suppressed. [Means for solving the problem]

[0006] In order to solve the above problems, the present inventors conducted research into thermosetting adhesive compositions and discovered that it is possible to suppress an increase in shear viscosity over time by applying a specific curing accelerator to a thermosetting adhesive composition, which led to the completion of the presently disclosed invention.

[0007] The present disclosure provides a thermosetting adhesive composition according to any one of [1] to [9], a laminated film according to

[10] , a method for producing a connection body according to

[11] and

[12] , and a connection body according to

[13] . [1] A thermosetting adhesive composition comprising an epoxy resin, an elastomer, and a curing accelerator, the curing accelerator being a compound that generates a heterocyclic amine compound upon heating. [2] The thermosetting adhesive composition according to [1], wherein the heterocyclic amine compound is an aromatic heterocyclic amine compound. [3] The thermosetting adhesive composition according to [1], wherein the heterocyclic amine compound is a compound having a pyrazole ring or a compound having an imidazole ring. [4] The thermosetting adhesive composition according to any one of [1] to [3], wherein the curing accelerator is a compound that is capable of deprotecting a protecting group by heating to generate a heterocyclic amine compound. [5] The thermosetting adhesive composition according to [4], wherein the protecting group is a substituted amide group. [6] The thermosetting adhesive composition according to any one of [1] to [5], which has a reaction rate of 50% or more after being heated at 95°C for 3 hours. [7] The thermosetting adhesive composition according to any one of [1] to [6], further comprising an epoxy resin curing agent, wherein the epoxy resin curing agent is a phenolic resin. [8] The thermosetting adhesive composition according to any one of [1] to [7], further comprising an inorganic filler. [9] The thermosetting adhesive composition according to any one of [1] to [8], having a shear viscosity at 95°C of 100 to 12,000 Pa s.

[10] A laminate film comprising a base film and an adhesive layer provided on a surface of the base film, the adhesive layer being composed of the thermosetting adhesive composition according to any one of [1] to [9].

[11] A method for producing a connection, comprising the steps of: (A) preparing a laminate comprising a first circuit member, a second circuit member, and an adhesive layer disposed between the first circuit member and the second circuit member; (B) heating the laminate at 90 to 110°C for 30 to 240 minutes; and (C) wire bonding the first circuit member and the second circuit member, in this order; wherein the adhesive layer is formed from a thermosetting adhesive composition according to any one of [1] to [9].

[12] The method for producing a connection body described in

[11] , wherein the first circuit member is one selected from the group consisting of a printed circuit board and a semiconductor chip, and the second circuit member is a flexible printed circuit board.

[13] A connection body comprising a first circuit member, a second circuit member, and an adhesive layer disposed between the first circuit member and the second circuit member, the adhesive layer being composed of a cured product of the thermosetting adhesive composition according to any one of [1] to [9]. Effect of the Invention

[0008] According to the present disclosure, there is provided a thermosetting adhesive composition in which the curing reaction proceeds sufficiently under low temperature conditions and furthermore, the increase in shear viscosity over time can be sufficiently suppressed. Also, according to the present disclosure, there is provided an adhesive film having an adhesive layer composed of such a thermosetting adhesive composition. Also, according to the present disclosure, there is provided a connection body using such a thermosetting adhesive composition and a manufacturing method thereof. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of a laminate film according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic state of a semiconductor module during a manufacturing process. [Diagram 3] FIG. 3 is a cross-sectional view showing a schematic state of a semiconductor module during a manufacturing process. [Figure 4] FIG. 4 is a perspective view that illustrates an example of a punched product according to the present disclosure. [Diagram 5] FIG. 5 is a cross-sectional view taken along line VV shown in FIG. [Figure 6] FIG. 6 is a cross-sectional view that illustrates a state in which an adhesive piece and a cover film that covers the adhesive piece are picked up from a base film. [Figure 7] FIG. 7 is a cross-sectional view showing a schematic state of a semiconductor module during a manufacturing process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the present embodiment will be described in detail with reference to the drawings. However, the present disclosure is not limited to the following embodiment. In the following embodiment, the components (including steps, etc.) are not essential unless otherwise specified. The same or equivalent parts are given the same reference numerals, and duplicated explanations are omitted. In addition, the positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings, unless otherwise specified. The size of the components in each figure is conceptual, and the relative relationship of the size between the components is not limited to that shown in each figure.

[0011] The same applies to the numerical values ​​and their ranges in the present disclosure, and the present disclosure is not limited thereto. In this specification, the numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit described in one numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with the value shown in the examples. In addition, the upper limit and lower limit values ​​described individually can be arbitrarily combined.

[0012] In this specification, the term "layer" includes a structure having a shape formed on the entire surface as well as a structure having a shape formed on a part of the surface when observed in a plan view. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.

[0013] In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl" and "(meth)acrylic acid". In addition, "(poly)" refers to both the case with and without the "poly" prefix.

[0014] "A or B" means that either A or B is contained, or both are contained. In addition, the materials exemplified below may be used alone or in combination of two or more, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0015] [Laminated film] Fig. 1 is a cross-sectional view showing a laminated film according to the present embodiment. The laminated film 10 shown in this figure includes a base film 1, an adhesive layer 3, and a cover film 5 in this order. The laminated film 10 has a width of 300 to 500 mm and a total length of 10 to 400 m, for example, and is produced by being wound into a roll. The structure of the laminated film 10 will be described below.

[0016] <Base film> The base film 1 is not particularly limited as long as it can sufficiently withstand the tension applied in the manufacturing process of the adhesive layer 3 and the manufacturing process of the semiconductor module. The base film 1 is preferably transparent from the viewpoint of visibility of the adhesive layer 3 disposed thereon. Examples of the base film 1 include polyester-based films such as polyethylene terephthalate films; polyolefin-based films such as homopolymers or copolymers, or mixtures thereof, such as polytetrafluoroethylene films, polyethylene films, polypropylene films, polymethylpentene films, polyvinyl acetate films, poly-4-methylpentene-1, ethylene-vinyl acetate copolymers, and ethylene-ethyl acrylate copolymers; and plastic films such as polyvinyl chloride films and polyimide films. The base film 1 may have a single-layer structure or a multilayer structure.

[0017] The thickness of the base film 1 may be appropriately selected within a range that does not impair workability, and may be, for example, 10 to 200 μm, 20 to 100 μm, or 25 to 80 μm. These thickness ranges are practically acceptable and economically effective.

[0018] In order to increase the adhesion of the adhesive layer 3 to the base film 1, the surface of the base film 1 may be subjected to a chemical or physical surface treatment such as corona treatment, chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, ionizing radiation treatment, etc. A film made of a fluororesin and having low surface energy may also be used as the base film 1. Examples of such a film include A-63 (release treatment agent: modified silicone-based) manufactured by Toyobo Film Solutions Co., Ltd. and A-31 (release treatment agent: Pt-based silicone-based) manufactured by Toyobo Film Solutions Co., Ltd.

[0019] In order to prevent the adhesive strength of the adhesive layer 3 to the base film 1 from becoming excessively high, a release layer composed of a release agent such as a silicone-based release agent, a fluorine-based release agent, or a long-chain alkyl acrylate-based release agent may be formed on the surface of the base film 1.

[0020] The adhesion between the base film 1 and the adhesive layer 3 is, for example, 0.5 N / m or more. When the adhesion is 0.5 N / m or more, it is easy to prevent the adhesive layer 3 from being inadvertently peeled off from the base film 1 during the process of producing the laminated film 10. The adhesion between the adhesive layer 3 and the base film 1 means the 90° peel strength, and specifically means the peel strength measured when a 20 mm wide sample having the adhesive layer 3 formed on the base film 1 is prepared, and this adhesive layer is peeled off from the base film at an angle of 90° at a peel speed of 50 mm / min.

[0021] <Adhesive layer> The adhesive layer 3 is used for bonding circuit members together, and is preferably used for bonding, for example, a printed circuit board and an end of an FPC board (flexible printed circuit board), or a semiconductor chip and an end of an FPC board. The module 50A (connection body) shown in FIG. 2 includes a semiconductor chip C, a printed circuit board 12 (first circuit member), an adhesive piece 3c, and an FPC board 15 (second circuit member). The adhesive piece 3c bonds the printed circuit board 12 and the end 15a of the FPC board 15. The adhesive piece 3c is composed of a cured product of the adhesive piece 3p (see FIG. 4). The adhesive piece 3p is obtained by processing the adhesive layer 3 shown in FIG. 1 into a predetermined shape by die cutting. The adhesive layer 16 bonds the printed circuit board 12 and the semiconductor chip C. The adhesive layer 16 may have the same composition as the adhesive piece 3c, or may have a different composition.

[0022] The module 50B shown in Fig. 3 is obtained by performing wire bonding on the module 50A shown in Fig. 2. A wire W1 electrically connects the semiconductor chip C and the printed circuit board 12, and a wire W2 electrically connects the printed circuit board 12 and the FPC board 15. The semiconductor chip C is, for example, a sensor chip. The printed circuit board 12 processes a signal from the semiconductor chip C. The signal from the printed circuit board 12 is transmitted to a tip portion 15a of the FPC board 15.

[0023] The adhesive piece 3p (adhesive layer) is composed of a thermosetting adhesive composition (hereinafter, may be simply referred to as "adhesive composition"). The adhesive composition contains an epoxy resin, an elastomer, and a curing accelerator. The curing accelerator is a compound that generates a heterocyclic amine compound when heated, and may be, for example, a compound that deprotects a protecting group when heated to generate a heterocyclic amine compound.

[0024] The shear viscosity (melt viscosity) of the adhesive composition at 95°C is 100 to 12000 Pa·s, and may be 200 Pa·s or more, 300 Pa·s or more, 400 Pa·s or more, or 500 Pa·s or more, and may be 10000 Pa·s or less, 8000 Pa·s or less, 6000 Pa·s or less, or 4000 Pa·s or less. When the shear viscosity at 95°C is within the above range, even if the tip portion 15a of the FPC board 15 has irregularities, the adhesive composition tends to be disposed without any gap between the tip portion 15a and the member to be bonded (printed circuit board 12).

[0025] The shear viscosity of the adhesive composition at 95°C can be measured, for example, by the following procedure. First, a plurality of film-like adhesives made of the adhesive composition with a thickness of 25 μm are prepared. Next, a plurality of film-like adhesives are laminated to a thickness of about 300 μm, and this laminate is punched out with a φ9 mm punch to prepare a measurement sample. A circular aluminum plate jig with a diameter of 8 mm is installed on a dynamic viscoelasticity device, and a measurement sample is set here. Next, the measurement is performed while raising the temperature to 100°C at a heating rate of 5°C / min while applying a 5% strain at 35°C, and the viscosity at 95°C is obtained, thereby measuring the shear viscosity at 95°C. In addition, in the measurement, the frequency is constant at 1 Hz, the initial load is held at 300 g, and the axial force is held at 100 g.

[0026] In order to adjust the shear viscosity at 95° C. to a predetermined range, for example, the following methods can be considered. Method 1: The amount of inorganic filler contained in the adhesive composition is made relatively small. Method 2: The amount of elastomer (e.g., acrylic rubber) contained in the adhesive composition is made relatively small. Method 3: The average particle size of the inorganic filler contained in the adhesive composition is made relatively large.

[0027] The adhesive composition may, for example, satisfy the following condition 1. ·Condition 1 After being heated at 95°C for 3 hours, the storage modulus at 95°C is 3 MPa or more.

[0028] It can be said that an adhesive composition that satisfies condition 1 has excellent low-temperature curing properties. This has the advantage that a material with a relatively low heat resistance can be used as a component that constitutes the module 50B. In order to obtain an adhesive composition that satisfies condition 1, for example, it is possible to use an epoxy resin as an epoxy resin curing agent together with an epoxy resin. The reason why the phenolic resin contributes to improving low-temperature curing properties is that the reactivity between a phenolic resin and an epoxy resin is higher than the reactivity between epoxy resins themselves, and the use of a phenolic resin facilitates the progress of the reaction.

[0029] By using an adhesive composition that satisfies condition 1, it is possible to reduce the shaking of the adhesive piece 3c during the wire bonding process, and wire bonding becomes easier to perform. As described above, the storage modulus related to condition 1 may be 3 MPa or more, 5 MPa or more, or 7 MPa or more. The storage modulus related to condition 1 may be, for example, 50 MPa or less. The higher the storage modulus related to condition 1, the easier it tends to be to perform wire bonding.

[0030] The adhesive composition may, for example, satisfy the following condition 2. ·Condition 2 After being heated at 95°C for 3 hours, the storage modulus at 35°C is 700MPa or less.

[0031] By using an adhesive composition that satisfies condition 2, the internal stress of the adhesive piece 3c is easily alleviated, and warping of the module 50B can be suppressed. As described above, the storage modulus according to condition 2 may be 700 MPa or less, 650 MPa or less, 600 MPa or less, or 550 MPa or less. The storage modulus according to condition 2 may be, for example, 50 MPa or more, 100 MPa or more, or 150 MPa or more.

[0032] In order to obtain an adhesive composition that satisfies condition 2, for example, the following method may be considered. Method 1: The adhesive composition contains a relatively large amount of elastomer (for example, acrylic rubber). Method 2: Use an elastomer with a relatively low glass transition temperature (Tg). Method 3: Use an epoxy resin with a flexible backbone.

[0033] According to the study by the present inventors, methods 1 and 2 are more effective than method 3. Regarding method 1, the content of the elastomer is, for example, 20 to 40 mass%, and may be 22 to 38 mass%, or 25 to 35 mass%, based on the total mass of the adhesive composition. Regarding method 2, the Tg of the elastomer is, for example, -50 to 20°C.

[0034] The storage modulus at 95°C and 35°C can be measured, for example, by the following procedure. First, a plurality of film-like adhesives made of an adhesive composition with a thickness of 25 μm are prepared. Next, a plurality of film-like adhesives are laminated to a thickness of about 300 μm, and the thickness is made into a size of 4 mm wide x 33 mm, and a measurement sample is prepared by heating at 95°C for 3 hours. The measurement sample thus prepared is set in a dynamic viscoelasticity device with a chuck distance of 20 mm, and a tensile load is applied to the measurement sample under the conditions of a frequency of 10 Hz and a heating rate of 3°C / min, and the storage modulus at 95°C and 35°C is measured.

[0035] It is preferable that the adhesive composition undergoes a curing reaction to some extent by heat treatment at 95° C. for 3 hours. The extent to which the reaction has progressed can be quantified by differential scanning calorimetry. That is, the reaction rate calculated by the following formula from the heat release amounts C1 and C2 respectively determined from a DSC curve obtained by differential scanning calorimetry at a heating rate of 10° C. / min is, for example, 50% or more, and may be 60% or more, or 70% or more. Reaction rate (%) = (C1-C2) / C1 x 100

[0036] The calorific value C1 is the calorific value (unit: J / g) measured for the adhesive composition. The calorific value C2 is the calorific value (unit: J / g) measured for the resin composition after the adhesive composition is heated at 95°C for 3 hours. The temperature range for differential scanning calorimetry is, for example, 30 to 300°C. The temperature range for determining the calorific values ​​C1 and C2 from the DSC curve obtained by measurement is 50 to 200°C. A reaction rate of 50% or more can suppress deterioration over time after the production process, and tends to be excellent in reliability.

[0037] The laminated film 10 can be produced, for example, as follows. First, a coating liquid is prepared by dissolving the adhesive composition constituting the adhesive layer 3 in a solvent such as an organic solvent to form a varnish. After this coating liquid is applied onto the base film 1, the solvent is removed to form the adhesive layer 3. Examples of the coating method include knife coating, roll coating, spray coating, gravure coating, bar coating, and curtain coating. Next, a cover film 5 is attached to the surface of the adhesive layer 3 under conditions of room temperature (25°C) to 60°C. This allows the laminated film 10 to be obtained. Note that the laminated film 10 can also be obtained by forming the adhesive layer 3 on a wide base film, and then laminating the cover film 5 to cover it to produce a laminated film, and then cutting (slitting) this to a predetermined width.

[0038] <Punching products> Fig. 4 is a perspective view showing a schematic diagram of a punched product produced from the laminated film 10. Fig. 5 is a cross-sectional view taken along line VV shown in Fig. 4. The punched product 20 shown in Figs. 4 and 5 comprises a strip-shaped base film 1 having a width of 100 mm or less, a plurality of adhesive pieces 3p arranged on the base film 1 in the longitudinal direction (the direction of arrow X shown in Fig. 4) of the base film 1, and a cover film 5p covering an upper surface 3f of the adhesive piece 3p and having the same shape as the adhesive piece 3p.

[0039] The adhesive piece 3p is suitably applied to bonding a circuit member (semiconductor chip or printed circuit board) to the tip of an FPC board. The area of ​​the adhesive piece 3p in a plan view is, for example, 1 to 100 mm 2 3 to 50 mm 2 Or 5~40mm 2 According to the punched product 20, it is possible to sequentially pick up a plurality of adhesive pieces 3p arranged in a line on the base film 1 (see FIG. 6), and then to arrange each adhesive piece 3p in a predetermined area of ​​the circuit member, thereby efficiently bonding the circuit member and the FPC member.

[0040] The punched product 20 can be obtained, for example, through the following steps. (a) A step of preparing a laminate film 10. (b) A step of obtaining a plurality of adhesive pieces 3p arranged on the base film 1 in the longitudinal direction of the base film 1 by die-cutting the adhesive layer 3 and the cover film 5 in the laminate film 10.

[0041] <Thermosetting adhesive composition (adhesive composition)> The adhesive composition constituting the adhesive layer 3 and the adhesive piece 3p will be described. As described above, the adhesive composition contains an epoxy resin, an elastomer, and a curing accelerator. The adhesive composition may further contain, for example, an epoxy resin curing agent, an inorganic filler, etc.

[0042] Epoxy resin Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, alicyclic epoxy resins, aliphatic chain epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, diglycidyl ethers of biphenols, diglycidyl ethers of naphthalene diols, diglycidyl ethers of phenols, diglycidyl ethers of alcohols, and difunctional epoxy resins such as alkyl substituted, halogenated, and hydrogenated products thereof, novolac type epoxy resins, etc. In addition, other commonly known epoxy resins such as polyfunctional epoxy resins and heterocyclic epoxy resins may be applied. In addition, components other than epoxy resins may be contained as impurities within a range that does not impair the properties.

[0043] The epoxy resin may contain, for example, an epoxy resin that is solid at 25° C. (hereinafter, may be referred to as a "solid epoxy resin"). That is, the epoxy resin may be composed of a solid epoxy resin and an epoxy resin that is liquid at 25° C. (hereinafter, may be referred to as a "liquid epoxy resin"). When the epoxy resin contains a solid epoxy resin, it tends to be less sticky during film formation, to be able to prevent the film from sticking to machines such as rolls, and to be able to prevent a decrease in workability when a laminated film is produced.

[0044] Specific examples of solid epoxy resins include YDCN-700-10 (manufactured by Nippon Steel Chemical & Material Co., Ltd., cresol novolac type epoxy resin), N-500P-10 (manufactured by DIC Corporation, cresol novolac type epoxy resin), HP-4710 (manufactured by DIC Corporation, naphthalene type epoxy resin), and NC-7000L (manufactured by Nippon Kayaku Co., Ltd., naphthalene type epoxy resin).

[0045] Specific examples of liquid epoxy resins include YDF-8170C (manufactured by Nippon Steel Chemical & Material Co., Ltd., bisphenol F type epoxy resin), EPICLON (registered trademark) series (EXA-830CRP, 830, 830-S, 835, etc.) (manufactured by DIC Corporation, bisphenol F type epoxy resin), and the like.

[0046] Epoxy resin hardener The epoxy resin curing agent may be a commonly used known curing agent. Examples of the epoxy resin curing agent include amines, polyamides, acid anhydrides, polysulfides, boron trifluoride, and phenol resins. The epoxy resin curing agent may be, for example, a phenol resin.

[0047] The phenolic resin is not particularly limited as long as it has a phenolic hydroxyl group in the molecule. Examples of the phenolic resin include novolac-type phenolic resins obtained by condensing or co-condensing phenols such as phenol, cresol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, etc. and / or naphthols such as α-naphthol, β-naphthol, dihydroxynaphthalene, etc. with a compound having an aldehyde group such as formaldehyde under an acid catalyst, allylated bisphenol A, allylated bisphenol F, allylated naphthalenediol, phenol novolac, phenol aralkyl resins synthesized from phenols such as phenol and / or naphthols and dimethoxyparaxylene or bis(methoxymethyl)biphenyl, naphthol aralkyl resins, biphenyl aralkyl-type phenolic resins, and phenyl aralkyl-type phenolic resins.

[0048] The total content of the epoxy resin and the epoxy resin curing agent (phenolic resin) is, for example, 35 to 70 mass %, and may be 40 to 65 mass %, or 45 to 60 mass %, based on the total amount of the adhesive composition. When the total content of the epoxy resin and the epoxy resin curing agent (phenolic resin) is within the above range, shrinkage due to thermal curing of the adhesive layer 3 can be suppressed, and excellent adhesion after thermal curing tends to be easily achieved.

[0049] The content of the epoxy resin is, for example, 10 to 40 mass%, or may be 15 to 35 mass%, or 20 to 30 mass%, based on the total amount of the adhesive composition. When the content of the epoxy resin is within the above range, sufficient thermosetting properties are obtained, and curing tends to proceed even at low temperatures.

[0050] The content of the solid epoxy resin relative to the total amount of the epoxy resin is, for example, 10 to 30 mass%, and may be 12 to 28 mass%, or 15 to 25 mass%. When the content of the solid epoxy resin is within the above range, the film is not sticky during film formation, and sticking to machines such as rolls can be suppressed, and a decrease in workability when a laminated film is produced tends to be suppressed.

[0051] The content of the solid epoxy resin is, for example, 2 to 10 mass%, or may be 3 to 8 mass%, or 4 to 6 mass%, based on the total amount of the adhesive composition. When the content of the solid epoxy resin is within the above range, the film is not sticky during film formation, and sticking to machines such as rolls can be suppressed, and a decrease in workability when a laminated film is produced tends to be suppressed.

[0052] Elastomer As the elastomer, a resin having thermoplasticity, or a resin having thermoplasticity at least in an uncured state and forming a crosslinked structure after heating can be used. From the viewpoint of excellent shrinkage, heat resistance, and peelability, the elastomer may be a (meth)acrylic copolymer having a reactive group (hereinafter, may be referred to as a "reactive group-containing (meth)acrylic copolymer").

[0053] When the elastomer contains a reactive group-containing (meth)acrylic copolymer, the adhesive composition may be in an embodiment that does not contain an epoxy resin, that is, the adhesive composition may be in an embodiment that contains a reactive group-containing (meth)acrylic copolymer and a curing accelerator.

[0054] Examples of the (meth)acrylic copolymer include (meth)acrylic acid ester copolymers such as acrylic glass and acrylic rubber. The (meth)acrylic copolymer may be acrylic rubber. The acrylic rubber may be formed by copolymerizing an acrylic acid ester as a main component and a monomer selected from a (meth)acrylic acid ester and acrylonitrile.

[0055] Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, etc. Examples of (meth)acrylic acid ester copolymers include copolymers containing butyl acrylate and acrylonitrile as copolymerization components, and copolymers containing ethyl acrylate and acrylonitrile as copolymerization components.

[0056] The reactive group-containing (meth)acrylic copolymer may be a reactive group-containing (meth)acrylic copolymer containing a (meth)acrylic monomer having a reactive group as a copolymerization component. Such a reactive group-containing (meth)acrylic copolymer can be obtained by copolymerizing a monomer mixture containing a (meth)acrylic monomer having a reactive group and the above-mentioned monomer.

[0057] From the viewpoint of improving heat resistance, examples of the reactive group include an epoxy group, a carboxyl group, a (meth)acryloyl group, a hydroxyl group, an episulfide group, etc. From the viewpoint of crosslinking property, the reactive group may be an epoxy group or a carboxyl group.

[0058] In this embodiment, the reactive group-containing (meth)acrylic copolymer may be an epoxy group-containing (meth)acrylic copolymer containing an epoxy group-containing (meth)acrylic monomer as a copolymerization component. In this case, the epoxy group-containing (meth)acrylic monomer may be glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, 3,4-epoxycyclohexylmethyl (meth)acrylate, etc. From the viewpoint of heat resistance, the reactive group-containing (meth)acrylic monomer may be glycidyl (meth)acrylate.

[0059] The glass transition temperature (Tg) of the elastomer is, for example, -50 to 20°C, and may be -30 to 15°C. When the Tg of the elastomer is -50°C or higher, it is easy to prevent the adhesive layer 3 from becoming excessively soft, and excellent handleability and adhesiveness can be achieved. On the other hand, when the Tg of the elastomer is 0°C or lower, it is easy to ensure the flexibility of the adhesive layer 3, and excellent adhesive strength can be achieved. In addition, even if there are irregularities on the adherend surface, the adhesive layer 3 easily follows the irregularities, and excellent adhesiveness can be achieved.

[0060] The Tg of an elastomer is a midpoint glass transition temperature obtained by differential scanning calorimetry (DSC). Specifically, the Tg of an elastomer is a midpoint glass transition temperature calculated by a method in accordance with JIS K7121:1987, by measuring the change in heat quantity under conditions of a temperature rise rate of 10°C / min and a measurement temperature of -80 to 80°C. In addition, when the elastomer is a commercially available product, the value described in the catalog or the like may be used.

[0061] The weight average molecular weight of the elastomer may be 100,000 to 2,000,000. When the weight average molecular weight is 100,000 or more, heat resistance is easily ensured. On the other hand, when the weight average molecular weight is 2,000,000 or less, a decrease in flow and a decrease in application are easily suppressed. The weight average molecular weight of the elastomer may be 400,000 to 1,500,000 or 500,000 to 1,200,000. The weight average molecular weight is a polystyrene-equivalent value obtained by using a calibration curve of standard polystyrene in gel permeation chromatography (GPC).

[0062] The content of the elastomer is, for example, 20 to 40 mass %, and may be 22 to 38 mass %, or 25 to 35 mass %, based on the total amount of the adhesive composition. When the content of the elastomer is within the above range, shrinkage associated with thermal curing of the adhesive layer 3 can be suppressed, and excellent adhesion after thermal curing tends to be easily achieved.

[0063] · Hardening accelerator The curing accelerator is a compound that generates a heterocyclic amine compound by heating. Examples of the curing accelerator include a compound that generates a heterocyclic amine compound by deprotecting a protecting group by heating (hereinafter, sometimes referred to as a "first compound"), and an ionic compound that generates a heterocyclic amine compound by heating (hereinafter, sometimes referred to as a "second compound"). The first compound can be said to be a compound in which an amino group contained in the heterocycle of a heterocyclic amine compound is protected by a protecting group. Among these, the curing accelerator may be the first compound.

[0064] In the adhesive composition containing the first compound or the second compound as a curing accelerator, a heterocyclic amine compound having a curing accelerating effect is generated by heating, and thermosetting properties are expressed. Therefore, even if the adhesive composition is not used immediately after preparation and is stored for a certain period of time, the curing reaction of the epoxy resin is sufficiently suppressed from progressing. That is, the increase in shear viscosity of the adhesive composition over time is sufficiently suppressed, and it is possible to maintain the usable state of the adhesive composition for a relatively long period of time (for example, more than two weeks) after preparation of the adhesive composition, and it is possible to realize a sufficiently long work life. In addition, the adhesive composition is also useful for realizing a heat curing treatment under a low temperature condition of 100 ° C or less. That is, a thermosetting resin having excellent low-temperature curing properties tends to easily undergo a curing reaction when stored in a state mixed with a curing accelerator. However, since the above-mentioned curing accelerator is deprotected by heating during use to express its function, the curing reaction of the epoxy resin is suppressed during storage. According to such an adhesive composition, it is possible to achieve both a long work life and low-temperature curing properties at a sufficiently high level.

[0065] Examples of the heterocyclic amine compound generated from the compound that generates a heterocyclic amine compound by heating include compounds having a pyrrolidine ring, a piperidine ring, a piperazine ring, a morpholine ring, an oxazine ring, a quinuclidine ring, a pyrrole ring, a pyrazole ring, an imidazole ring, a pyridine ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, an oxazole ring, a thiazole ring, etc. In these rings, some of the hydrogen atoms directly bonded to the carbon atoms constituting the ring may be substituted with a substituent. The substituent is a group commonly used in the field of organic chemistry. Examples of the substituent include a halogen atom, a hydroxy group, an amino group, a sulfonic acid group, a nitro group, a cyano group, an alkyl group, an aryl group, an alkoxy group, a substituted amino group, etc. Among these, the heterocyclic amine compound may be, for example, an aromatic heterocyclic amine compound, and may be, for example, a compound having a pyrazole ring or a compound having an imidazole ring.

[0066] The protecting group in the first compound is a protecting group that protects the amino group contained in the heterocycle of the heterocyclic amine compound. The protecting group can be a group that is generally used as a protecting group for amino groups in the field of organic chemistry. Examples of the protecting group include a tosyl group, a methoxymethyl group, a benzyloxymethyl group, an allyl group, a triisopropylsilyl group, a benzyl group, a methoxycarbonyl group, a p-methoxybenzyl group, and a p-methoxyphenyl group.

[0067] The protecting group in the first compound may, in one embodiment, be a substituted amide group. A substituted amide group is, for example, -C(O)N(R 1 )(R 2 ) represented by the group (R 1 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms in which some of the hydrogen atoms directly bonded to a carbon atom may be substituted with a (meth)acryloyloxy group, R 2 represents an alkyl group having 1 to 10 carbon atoms in which some of the hydrogen atoms directly bonded to the carbon atom may be substituted with (meth)acryloyloxy groups.

[0068] Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an isopropyl group, and an isobutyl group.

[0069] Specific examples of the first compound include Karenz MOI-BP (trade name, manufactured by Resonac Corporation, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl methacrylate, "Karenz" is a registered trademark), Karenz AOI-BP (trade name, manufactured by Resonac Corporation, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl acrylate), and the like.

[0070] Examples of the second compound include pyrazonium salt compounds, imidazolium salt compounds, etc. Specific examples of the second compound include EMZ-K (trade name, manufactured by Hokko Sangyo Co., Ltd., 2-ethyl-4-methylimidazolium tetraphenylborate, "EMZ-K" is a registered trademark), etc.

[0071] The content of the curing accelerator is, for example, 0.1 to 20 mass%, or may be 1 to 18 mass%, or 3 to 15 mass%, based on the total amount of the adhesive composition. When the content of the curing accelerator is within the above range, the effects of the present disclosure tend to be sufficiently exhibited.

[0072] Inorganic fillers The inorganic filler can be selected according to the desired function. Examples of the inorganic filler include metal (conductive) fillers such as silver powder, gold powder, and copper powder; and nonmetal (insulating) fillers such as silica, alumina, boron nitride, titania, glass, iron oxide, and ceramics. The inorganic filler may be, for example, a silica filler.

[0073] The surface of the inorganic filler may have an organic group. By modifying the surface of the inorganic filler with an organic group, the dispersibility in an organic solvent when preparing a varnish for forming the adhesive layer 3 can be improved. In addition, the shrinkage caused by the thermal curing of the adhesive layer 3 can be suppressed, and the adhesive layer 3 tends to have both a high elastic modulus and excellent releasability. The inorganic filler having an organic group on its surface can be obtained, for example, by mixing a silane coupling agent represented by the following formula (B-1) with the inorganic filler and stirring at a temperature of 30°C or higher. The fact that the surface of the inorganic filler is modified with an organic group can be confirmed by ultraviolet-visible spectroscopy, infrared absorption spectroscopy, X-ray photoelectron spectroscopy, etc.

[0074] [ka]

[0075] In formula (B-1), X represents an organic group selected from the group consisting of a phenyl group, a glycidoxy group, a (meth)acryloyloxy group, a mercapto group, an amino group, a vinyl group, an isocyanate group, and a methacryloxy group, s represents 0 or an integer of 1 to 10, and R 11 , R 12 , and R 13 each independently represents an alkyl group having 1 to 10 carbon atoms.

[0076] The alkyl group having 1 to 10 carbon atoms may be the same as the alkyl group having 1 to 10 carbon atoms exemplified above for the substituted amide group.

[0077] From the viewpoint of availability, the alkyl group having 1 to 10 carbon atoms may be a group selected from the group consisting of a methyl group, an ethyl group, and a pentyl group. From the viewpoint of heat resistance, X may be a group selected from the group consisting of an amino group, a glycidoxy group, a mercapto group, and an isocyanate group, and may be a glycidoxy group or a mercapto group.

[0078] s may be an integer of 0 to 5, or may be an integer of 0 to 4, from the viewpoint of suppressing the fluidity of the film at high temperatures and improving the heat resistance.

[0079] The content of the inorganic filler is 1 to 25% by mass based on the total amount of the adhesive composition. When the content of the inorganic filler is 25% by mass or less based on the total amount of the adhesive composition, the adhesive strength with a resin member or the like tends to be sufficient. When the content of the inorganic filler is 1% by mass or more based on the total amount of the adhesive composition, the adhesive strength of the adhesive composition tends to be too high, and the workability tends to be suppressed from being reduced. The content of the inorganic filler may be 2% by mass or more, 3% by mass or more, 5% by mass or more, or 7% by mass or more based on the total amount of the adhesive composition, and may be 20% by mass or less, 15% by mass or less, 12% by mass or less, or 10% by mass or less.

[0080] The adhesive composition may further contain other components. Examples of the other components include coupling agents such as silane coupling agents, and organic fillers such as carbon, rubber-based fillers, silicone-based fine particles, polyamide fine particles, and polyimide fine particles. The content of the other components may be 0 to 30% by mass based on the total amount of the adhesive composition.

[0081] Organic solvents The adhesive composition may be diluted with an organic solvent as necessary, or may be used as an adhesive varnish. The organic solvent is not particularly limited, but can be determined in consideration of the volatility during film formation from the boiling point. Examples of organic solvents include relatively low boiling point solvents such as methanol, ethanol, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, methyl ethyl ketone, acetone, methyl isobutyl ketone, toluene, and xylene; and relatively high boiling point solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and cyclohexanone. Solvents with relatively low boiling points have the advantage that the film is less likely to harden during film formation. Solvents with relatively high boiling points have the advantage of improving film formability.

[0082] The thickness of the adhesive layer 3 may be appropriately selected within a range that does not impair workability, and may be, for example, 1 to 200 μm, 5 to 150 μm, or 10 to 150 μm. When the thickness of the adhesive layer 3 is 1 μm or more, sufficient adhesion is easily ensured, while when the thickness is 200 μm or less, there is a tendency that the adhesive composition constituting the adhesive layer 3 is easily prevented from protruding from the base film 1 or the cover film 5.

[0083] <Cover film> There is no particular restriction on the cover film 5 so long as it can be easily peeled off from the adhesive layer 3. Examples of the cover film 5 include polyester films such as polyethylene terephthalate film; polyolefin films such as homopolymers or copolymers, or mixtures thereof, such as polytetrafluoroethylene film, polyethylene film, polypropylene film, polymethylpentene film, polyvinyl acetate film, poly-4-methylpentene-1, ethylene-vinyl acetate copolymer, and ethylene-ethyl acrylate copolymer; and plastic films such as polyvinyl chloride film and polyimide film. The cover film 5 may have a single layer structure or a multilayer structure.

[0084] When the cover film 5 has a multi-layer structure, it may be an adhesive film, specifically, an adhesive film for dicing (manufactured by Maxell, Ltd.). The adhesive film may have an adhesive layer and a base layer. In this case, the adhesive layer may be configured to contact the adhesive layer 3. The adhesive layer may be a photocurable adhesive layer or a non-photocurable adhesive layer, and the base layer may be the above-mentioned plastic film or the like.

[0085] The adhesion between the adhesive layer 3 and the cover film 5 is, for example, 70 N / m or less, and may be 50 N / m or less or 20 N / m or less. In particular, when the adhesive layer 3 is made of an adhesive composition, it is preferable that the adhesion of the cover film 5 to the adhesive layer 3 is in the above range after heat treatment at 75 ° C. for 1 second. When the adhesion is 70 N / m or less, the adhesive layer 3 covered with the cover film 5 is temporarily pressed to an adherend (for example, a substrate) under conditions of 75 ° C. for 0.5 seconds, and then the cover film 5 can be easily peeled off from the semi-cured adhesive layer 3 with an adhesive tape or the like. The adhesion of the cover film 5 to the adhesive layer 3 means a 90 ° peel strength, and specifically, it means a peel strength measured when a sample is prepared in which a cover film of the same width is arranged on an adhesive layer of 20 mm width made of the same composition as the adhesive layer 3, and the cover film is peeled off from the adhesive layer at an angle of 90 ° and at a peeling speed of 50 mm / min. When the cover film 5 is an adhesive film having a photocurable adhesive layer, the adhesive strength may be the value after irradiation with light.

[0086] The thickness of the cover film 5 may be appropriately selected within a range that does not impair workability, and may be, for example, 10 to 200 μm, 10 to 180 μm, or 15 to 140 μm. These thickness ranges are practically acceptable and economically effective.

[0087] [Manufacturing method of connection body (semiconductor module)] A method for producing the module 50B (connection body) shown in FIG. 3 using the punched product 20 will be described. FIG. 6 is a cross-sectional view that shows a schematic state in which the adhesive piece 3p and the cover film 5p covering it are picked up from the base film 1. With a certain tension applied to the punched product 20, the punched product 20 is moved in the direction of the arrow shown in FIG. 6 while the surface of the punched product 20 facing the base film 1 is abutted against a wedge-shaped member 60. As a result, as shown in FIG. 6, the adhesive piece 3p and the front of the cover film 5p are raised above the base film 1. In this state, the adhesive piece 3p and the cover film 5p are picked up, for example, by a pickup device 65 having suction force.

[0088] Next, the adhesive piece 3p covered with the cover film 5p is placed on the surface 12a of the printed circuit board 12 (see FIG. 7). Thereafter, the adhesive piece 3p is provisionally pressure-bonded to the printed circuit board 12. The provisional pressure-bonding can be performed, for example, under conditions of a temperature of 60 to 85°C and a pressure of 0.1 to 2 MPa for 0.1 to 10 seconds. The provisional pressure-bonding semi-cures the adhesive piece 3p, thereby improving its adhesive strength to the surface 12a. Thereafter, the cover film 5p is peeled off from the adhesive piece 3p using an adhesive tape or the like. This exposes the surface F1 of the adhesive piece 3p.

[0089] The adhesion of the tip 15a of the FPC board 15 to the printed circuit board 12 includes a step of pressing the tip 15a against the adhesive piece 3p, and then a step of curing the adhesive piece 3p by heating. That is, first, the tip 15a of the FPC board 15 is placed on the upper surface 3f of the adhesive piece 3p, and then the tip 15a is pressed against the adhesive piece 3p. This results in a laminate including the printed circuit board 12, the FPC board 15, and the adhesive piece 3p (step (A)). The pressing can be performed, for example, for 0.1 to 10 seconds under conditions of a temperature of 60 to 85°C and a pressing force of 0.1 to 3 MPa.

[0090] Next, the adhesive piece 3p is cured. The curing can be performed, for example, at a temperature of 90 to 110°C for 30 to 240 minutes. As a result, the adhesive piece 3p becomes an adhesive piece 3c composed of a cured product of the adhesive composition, and the module 50A shown in FIG. 2 is obtained (step (B)). From the viewpoint of the heat resistance of the members constituting the module 50A, the heating conditions in the above conditions 1 and 2 are set to 95°C for 3 hours. By relatively lowering the temperature to which the module 50A is heated, there is an advantage in that the selection of materials is expanded.

[0091] Wire bonding is performed on the module 50A (step (C)). This results in the module 50B shown in FIG. 3. The semiconductor module is then completed through a process in which the wires W1 and W2 of the module 50B are protected with a resin material, a heat treatment that promotes a curing reaction of the adhesive piece 3c, and the like. When manufacturing a connection body using this adhesive piece, steps (A), (B), and (C) can be performed in sequence.

[0092] Although the embodiment of the present disclosure has been described in detail above, the present disclosure is not limited to the above embodiment. For example, in the above embodiment, the adhesive piece 3p made of the adhesive composition is prepared in advance by die cutting, but the adhesive layer may be formed by preparing a coating liquid containing the adhesive composition and coating the coating liquid on the surface of the printed circuit board 12. EXAMPLES

[0093] The present disclosure will be specifically described below using examples, but the present disclosure is not limited to these examples.

[0094] (Examples 1 to 3) [Making laminated films] <Material preparation> To prepare the adhesive varnish of the example, the following materials were prepared: (1) Epoxy resin EXA-830CRP (product name, manufactured by DIC Corporation, bisphenol F type epoxy resin, epoxy equivalent: 160g / eq, liquid at 25℃) N-500P-10 (product name, manufactured by DIC Corporation, cresol novolac type epoxy resin, epoxy equivalent: 204g / eq, solid at 25℃) (2) Epoxy resin hardener MEH-7800-4S (product name, manufactured by Meiwa Chemical Industry Co., Ltd., xylylene type phenolic resin, hydroxyl equivalent: 170g / eq) (3) Elastomer HTR-860P-3CSP (product name, Nagase ChemteX Corporation, acrylic resin, weight average molecular weight: 800,000, Tg: 12°C) (4) Curing accelerator Karenz MOI-BP (trade name, manufactured by Resonac Corporation, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl methacrylate, "Karenz" is a registered trademark) (5) Inorganic filler SC-2050-HLG (product name, manufactured by Admatechs Co., Ltd., surface treatment filler) (6) Solvent Cyclohexanone

[0095] An adhesive varnish was obtained by mixing the materials and solvent shown in Table 1 and degassing under vacuum. This adhesive varnish was applied onto a 38 μm thick surface release-treated PET film as a base film. After a drying process, a film-like adhesive (adhesive layer) of 25 μm thick was formed on one side of the PET film, and a dicing adhesive film (manufactured by Maxell Co., Ltd.) was attached as a cover film to the surface of the film-like adhesive, thereby obtaining laminated films of Examples 1 to 3, which include a base film, an adhesive layer, and a cover film. A plurality of laminated films were prepared.

[0096] [Evaluation of laminated film] <Measurement of reaction rate> The reaction rate of the film-like adhesive was measured by the following method. That is, 10 mg of the film-like adhesive was weighed in an aluminum pan (manufactured by Epolead Service Co., Ltd.), an aluminum lid was placed on the pan, and the evaluation sample was sealed in the sample pan using a crimper. Using a differential scanning calorimeter (Thermo plus DSC8235E, manufactured by Rigaku Co., Ltd.), DSC was measured in a nitrogen atmosphere at a heating rate of 10°C / min and a measurement temperature range of 30 to 300°C. The partial area analysis method was used as a means of analyzing the amount of heat generated. The total amount of heat generated (unit: J / g) was calculated by specifying the baseline of the analysis temperature range and integrating the peak area by instructing the analysis in the temperature range of 50 to 200°C of the DSC curve. This was defined as the initial amount of heat generated C1.

[0097] Next, the film-like adhesive (initial sample) was placed in an oven set at 95°C and heat-treated for 3 hours. Using the sample after heat treatment, the calorific value (unit: J / g) from 50 to 200°C was calculated using the same procedure as before heat treatment, as described above, and this was designated as the calorific value C2 after heat treatment. The reaction rate was calculated using the following formula using the two obtained values ​​of calorific values ​​C1 and C2. The results are shown in Table 1. Reaction rate (%) = (C1-C2) / C1 x 100

[0098] <Measurement of shear viscosity (melt viscosity)> The shear viscosity of the film-like adhesive (in the B-stage state before heating) at 95°C was measured by the following method. That is, a plurality of 25μm-thick film-like adhesives were laminated to a thickness of about 300μm, and this laminate was punched out with a φ9mm punch to prepare a sample. A circular aluminum plate jig with a diameter of 8mm was installed on a dynamic viscoelasticity device ARES (manufactured by TA instruments), and the above sample was set on it. Thereafter, the shear viscosity at 95°C was measured while heating to 100°C at a heating rate of 5°C / min while applying a 5% strain at 35°C. The frequency was kept constant at 1Hz, the initial load was kept at 300g, and the axial force was kept at 100g. The results are shown in Table 1.

[0099] <Measurement of storage modulus> After the film-like adhesive was heated at 95°C for 3 hours, the storage modulus of the film-like adhesive was measured by the following method. That is, a plurality of 25 μm thick film-like adhesives were laminated to a thickness of about 300 μm, which was cut into a size of 4 mm wide x 33 mm, and cured at 95°C for 3 hours to obtain a sample for measurement. The sample was set in a dynamic viscoelasticity device (product name: Rheogel E-4000, manufactured by UBM Co., Ltd.) with a chuck distance of 20 mm, and a tensile load was applied, and measurements were performed at a frequency of 10 Hz and a heating rate of 3°C / min to measure the storage modulus at 95°C and 35°C. The results are shown in Table 1.

[0100] <Measurement of die shear strength> The die shear strength of the film-like adhesive after curing was measured by the following method. A dicing tape (manufactured by Resonac Co., Ltd., thickness 110 μm) having a base film and an adhesive layer was prepared, and the prepared film-like adhesive (thickness 25 μm) was attached to the dicing tape to prepare a dicing-die bonding integrated film comprising a dicing tape and an adhesive layer made of a film-like adhesive provided on the adhesive layer of the dicing tape. Next, a semiconductor wafer (thickness 400 μm) was laminated on the adhesive layer side of the dicing-die bonding integrated film at a stage temperature of 70°C to prepare a dicing sample.

[0101] The prepared diced sample was cut using a fully automatic dicer DFD-6361 (manufactured by Disco Corporation). Cutting was performed by a step-cut method using two blades, and dicing blades ZH05-SD2000-N1-FF and ZH05-SD2000-N1-EE (both manufactured by Disco Corporation) were used. The cutting conditions were a blade rotation speed of 4000 rpm, a cutting speed of 50 mm / sec, and a chip size of 5 mm x 5 mm. The first cutting step was performed so that about 200 μm of the semiconductor wafer remained, and then the second cutting step was performed so that about 20 μm of the dicing tape was cut.

[0102] Next, a semiconductor chip formed from the semiconductor wafer was picked up using a pickup collet. The pickup was performed by pushing up using one central pin. The pickup conditions were a push-up speed of 20 mm / s and a push-up height of 450 μm. In this way, a semiconductor chip with an adhesive piece was obtained.

[0103] The obtained semiconductor chip with adhesive piece was used to measure the die shear strength after curing. The semiconductor chip was thermally bonded onto a solder resist (Taiyo Holdings Co., Ltd., product name: AUS-308). The bonding conditions were a temperature of 95°C, a time of 1 second, and a pressure of 0.6 MPa. The sample obtained by bonding was then placed in a dryer and cured by heating at 95°C for 3 hours. The cured sample was then measured for the die shear strength after curing between the semiconductor chip and the solder resist by hooking and pulling the semiconductor chip with a universal bond tester (manufactured by Nordson Advanced Technology Co., Ltd., product name: Series 4000). The measurement conditions were 6.7 MPa / sec, and the stage temperature was 95°C. The results are shown in Table 1.

[0104] [Table 1]

[0105] <Evaluation of changes in shear viscosity over time> The shear viscosity at 95°C of the film adhesive of Example 1 was measured every week. That is, eight test pieces having a predetermined size were prepared by cutting out from the film adhesive. They were laminated using a rubber roll on a hot plate at 70°C to prepare a laminate with a thickness of 300 μm. This laminate was punched out with a φ9 mm punch to prepare a sample. The sample was attached to the measurement jig of a rotational viscoelasticity measuring device (manufactured by TA Instruments Japan Co., Ltd., product name: ARES-RDA). The gap of the measurement jig was adjusted so that the load applied to the sample at this point was 10 to 15 g. The viscoelasticity of the sample was then measured under the following conditions. The measurement was continued until two weeks had passed, and the sample was left at room temperature (25°C) until the measurement was carried out. The results are shown in Table 2. Measurement conditions: Disc plate: Aluminum, circular (8mmφ) Measurement frequency: 1Hz Heating rate: 5℃ / min Distortion: 5% Measurement temperature: 35~100℃ Initial load: 300g

[0106] [Table 2]

[0107] As shown in Table 1, it was found that the curing reaction of the adhesive compositions of Examples 1 to 3 proceeds sufficiently under low temperature conditions of 100°C or less. Furthermore, as shown in Table 2, the adhesive composition of Example 1 did not observe an increase in shear viscosity even after 2 weeks. It is presumed that the adhesive compositions of Examples 2 and 3, which contain a lower amount of curing accelerator than Example 1, also show a similar tendency. From the above results, it was confirmed that the thermosetting adhesive composition of the present disclosure allows the curing reaction to proceed sufficiently under low temperature conditions, and furthermore, it is possible to sufficiently suppress an increase in shear viscosity over time. [Explanation of symbols]

[0108] 1...base film, 3...adhesive layer, 3c, 3p...adhesive piece, 5, 5p...cover film, 10...laminated film, 12...printed circuit board, 15...FPC board, 15a...tip portion, 20...punched product, 50A, 50B...module (connector), C...semiconductor chip, W1, W2...wires.

Claims

1. Contains an epoxy resin, an elastomer, and a curing accelerator, The curing accelerator is a compound that generates a heterocyclic amine compound by heating. A thermosetting adhesive composition.

2. The heterocyclic amine compound is an aromatic heterocyclic amine compound. The thermosetting adhesive composition of claim 1 .

3. The heterocyclic amine compound is a compound having a pyrazole ring or a compound having an imidazole ring. The thermosetting adhesive composition of claim 1 .

4. The curing accelerator is a compound that deprotects a protecting group by heating to generate a heterocyclic amine compound. The thermosetting adhesive composition according to any one of claims 1 to 3.

5. the protecting group is a substituted amide group; The thermosetting adhesive composition according to claim 4.

6. The reaction rate is 50% or more after heating at 95°C for 3 hours. The thermosetting adhesive composition according to any one of claims 1 to 3.

7. Further containing an epoxy resin hardener, The epoxy resin curing agent is a phenolic resin. The thermosetting adhesive composition according to any one of claims 1 to 3.

8. Further containing an inorganic filler, The thermosetting adhesive composition according to any one of claims 1 to 3.

9. The shear viscosity at 95°C is 100 to 12,000 Pa·s. The thermosetting adhesive composition according to any one of claims 1 to 3.

10. A base film; an adhesive layer provided on a surface of the base film; Equipped with The adhesive layer is composed of the thermosetting adhesive composition according to any one of claims 1 to 3. Laminated film.

11. (A) providing a laminate comprising a first circuit member, a second circuit member, and an adhesive layer disposed between the first circuit member and the second circuit member; (B) heating the laminate at 90 to 110° C. for 30 to 240 minutes; (C) wire bonding the first circuit member and the second circuit member; in this order, The adhesive layer is composed of the thermosetting adhesive composition according to any one of claims 1 to 3. A method for manufacturing a connector.

12. The first circuit member is one selected from the group consisting of a printed circuit board and a semiconductor chip, and the second circuit member is a flexible printed circuit board. The method for producing the connection body according to claim 11 .

13. a first circuit member; a second circuit member; an adhesive layer disposed between the first circuit member and the second circuit member; Equipped with The adhesive layer is composed of a cured product of the thermosetting adhesive composition according to any one of claims 1 to 3. Connection body.

Citation Information

Patent Citations

  • Die-bond dicing sheet

    JP2007288170A

  • Pressure-sensitive adhesive sheet

    JP2009209345A